(untitled) (Global Journal of Science Frontier Research, 2018)
A cross-sectional study was conducted from November 2010 to April 2011 with the objective of identifying the major ixodid tick species of domestic ruminants, estimating their prevalence and investigating their associated risk factors in SodoZuria, Damot Gale and Humbo districts of Wolaita zone, Southern Ethiopia. A total of 384 ruminants comprising 138 cattle, 130 sheep and 116 goats were examined in the study areas. An overall prevalence of tick infestation in the three study districts was 89.1% in cattle, 70 % in sheep and 32.8% in goats. The difference in the prevalence of tick infestation between the three species of ruminants was statistically significant (P0.05) except for goats in which the prevalence was significantly (p0.05) associated with the age of animals. In this study, six species of ixodid ticks which belong to three genera were identified in all the three ruminants. These are Amblyomma variegatum, Amblyomma gemma, Amblyomma lepidium, Amblyomma cohaerence, Rhipicephalu evertsi evertsi and Boopphilu decoloratus.